ANALISIS HUBUNGAN ANTARA KEGIATAN MELUKIS DENGAN KEBUTUHAN PSIKOLOGIS PADA REMAJA - Nunuk Nur Shokiyah (Institut Seni Indonesia Surakarta, 2014)
This research aims to learn the correlation between painting activities and psychological needs to the teens.There are two variables in this research covering painting activities as the independent variable and psychologicalneeds as the dependent variable. The correlation technique of Product Moment Pearson is used to know thecorrelation between painting activities and the psychological needs to the teens, while the calculation usesthe computer program SPSS 15 for windows release. Subject of this research is all active students of thePure Fine Arts Department in Institut Seni Indonesia Surakarta. All data that is collected covers 61 subjects.The measuring instrument that is used is the intensity scale of painting activities and the scale of psychologicalneeds. The result of this research shows the coefficient correlation (rxy = 0,746; p = 0.000), it means thatthere is a significant correlation between the painting activities and the psychological needs to the teens.Meanwhile, the determination coefficient of the correlation is R2 is 0,556. It means that the painting activitiesgive the effective contribution to the psychological needs to the teens as much as 55,6 % while the rest of44,6 % is determined by other variables.Keywords: painting activities, psychological needs.